Exploring frontline work in China. (17th July 2017) - Zang, Xiaowei; Musheno, Michael
Abstract : This study of the state frontline workforce breaks new ground by conducting an institutional analysis of rule abidance in the People's Republic of China (PRC). We draw upon a survey ( n = 1, 721) of Chengguan officers, the main players in regulatory enforcement of civil law in urban China, to explore the influence of autocratic one‐party rule on the meaning of and variation in rule abidance in China. The majority of Chengguan officers are rule followers, and demographic differences show little deviation from this norm. However, institutional factors associated with one‐party rule, particularly upward accountability, the privilege of administrative rank, and unequal access to power and resources, are significant in shaping differences in rule following among Chengguan officers. We conclude with a discussion of the similarities in institutional pressures on urban regulatory policing in China and the United States.